2007
DOI: 10.2527/jas.2006-208
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oscillating dietary protein concentrations on finishing cattle. II. Nutrient retention and ammonia emissions

Abstract: ABSTRACT:We hypothesized that oscillation of the dietary CP concentrations would improve efficiency of N use and reduce N loss to the environment. Charolaiscross steers (n = 8; 315 ± 21 kg of BW) were used in a replicated 4 × 4 Latin square design. The steers were allowed ad libitum access to the following diets: 1) 9.1% CP (low), 2) 11.8% CP (medium), 3) 13.9% CP (high), or 4) low and high oscillated on a 48-h interval on each diet (oscillating). Dry matter intake did not differ among treatments (P = 0.46), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 29 publications
9
63
0
Order By: Relevance
“…However, Brown et al (2005) reported that DMI was not affected by protein levels who fed diets containing 21-30% CP to Holstein heifer calves. Similarly, Archibeque et al (2007b) showed that DMI did not differ among treatments (p=0.46), but N intake differed (P<0.01) from (Allen 1997).…”
Section: Nutrients Intakementioning
confidence: 79%
“…However, Brown et al (2005) reported that DMI was not affected by protein levels who fed diets containing 21-30% CP to Holstein heifer calves. Similarly, Archibeque et al (2007b) showed that DMI did not differ among treatments (p=0.46), but N intake differed (P<0.01) from (Allen 1997).…”
Section: Nutrients Intakementioning
confidence: 79%
“…Archibeque et al [16] measured a significant 66% reduction of in vitro ammonia volatilization from fresh composite manure and urine samples from an oscillating CP treatment compared to a high CP treatment with no reduction in animal performance [28]. Archibeque et al [16] studied an oscillating treatment that averaged 11.5% CP, and found no difference in the volatilization of ammonia or animal performance between the oscillating treatment and a moderate CP treatment with a constant 11.8% CP. In addition, the timing and the magnitude of the oscillation was considerably different, switching from 9.1% CP to 13.9% CP on a predictable 48 h rotation [16].…”
Section: Ammonia Fluxmentioning
confidence: 99%
“…Archibeque et al [16] studied an oscillating treatment that averaged 11.5% CP, and found no difference in the volatilization of ammonia or animal performance between the oscillating treatment and a moderate CP treatment with a constant 11.8% CP. In addition, the timing and the magnitude of the oscillation was considerably different, switching from 9.1% CP to 13.9% CP on a predictable 48 h rotation [16]. The current study fed an 11.62% CP diet every Wednesday, Thursday, and Saturday and a 13.5% CP diet the remaining days of the week.…”
Section: Ammonia Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedlot diets containing DDGS tend to be higher in protein than NRC recommendations, often reaching levels of 15 to 18% CP. Several recently published articles evaluated the effects of protein concentrations in beef cattle diet on ammonia emissions and manure quality (Cole et al, 2005;Todd et al, 2006;Archibeque et al, 2007;Spiehs et al, 2012), but the impact of dietary protein levels on the manure concentrations and GHG emissions is deficient. In particular, in the Northern Plains with abundant DDGS, no research has been done comparing the effect of a high protein diet and NRC-recommended protein diet fed to cattle on manure composition and GHG emissions from the feedlot surfaces.…”
Section: Introductionmentioning
confidence: 99%